Historical European Martial Art a crossroad between academic research, martial heritage re-creation and martial sport practices - Jaquet Daniel; Sørensen Claus Frederik (Bern Open Publishing, 2015)
Historical European martial arts (HEMA) have to be considered an important part of our common European cultural heritage. Studies within this field of research have the potential to enlighten the puzzle posed by past societies, for example in the field of history, history of science and technology, or fields related to material culture.